Cisplatin plus capecitabine concomitant with intensity-modulated radiation therapy in non-metastatic anal squamous cell carcinoma: the experience of a single research cancer center. (July 2020) - Rotundo, Maria Saveria; Zampino, Maria Giulia; Ravenda, Paola Simona; Bagnardi, Vincenzo; Peveri, Giulia; Dell'Acqua, Veronica; Surgo, Alessia; Trovato, Cristina; Bottiglieri, Luca; Bertani, Emilio; Petz, Wanda Luisa; Fumagalli Romario, Uberto; et al.
Background and Aims: The standard treatment of non-metastatic anal squamous cell carcinoma (ASCC) consists of chemotherapy with mitomycin (MMC) plus 5-fluorouracil (5FU) for 1–2 cycles concomitant with pelvic radiotherapy. Subsequent studies introduced cisplatin (CDDP) combined with 5FU, with unclear results. We evaluated the doublet capecitabine (C) and CDDP as a possible alternative to MMC-5FU regimen concomitant with intensity-modulated radiation therapy (IMRT). Patients and Methods: We carried out a retrospective study on 67 patients affected by stage I–III ASCC, treated with CDDP (60–70 mg/m 2 every 21 days for two courses) plus C (825 mg/m 2 twice daily for 5 days/week) chemotherapy concomitant with IMRT for curative intent. Results: At a median follow up of 41 months, the clinical complete response calculated at the 6-month time-point (6-moCR), the 6-month objective response rate and the 6-month disease control rate were 93%, 94%, and 99%, respectively. Disease-free survival rates at 1, 2, and 3 years were 89%, 87%, and 85%, while the overall survival rates at 1 and 2 years were 100% and 95%. The colostomy-free survival rates were 90% at 1 year and 88% at 2 years. Grade 3–4 acute adverse events were reported in 61% of patients; predominantly skin toxicity (46%) and limited hematological toxicity (12%). Conclusion: In this retrospective study, chemotherapy with C plus CDDP concomitant with IMRT proved safe and effective, and may represent a possible alternative option to standard MMC-containing regimen for curative intent.